Islamic Perspectives in the Provision of Wages (Ujrah) (Empirical Study of The Qur'an and Interpretation) - Julita Julita; Lailan Safina Hasibuan (AIBPM Publisher, 2022)
Economic wages are the price that must be paid to employees for their services in the production of wealth, like other factors of production, in other words, wages are the price of labor paid for their services and production. To clarify the position of wages, the Ministry of Manpower through the Decree of the Minister of Manpower No. 13 of 2003 concerning the minimum wage explains several functions of wages, including; First, wages function to meet minimum basic needs for workers and their families. Second, employers in providing labor wages are calculated based on the results of production. Third, in industrial relations Pancasila, labor wages are not only part of the production costs but also have a social function, namely to meet the needs of a decent life for workers and their families. Fourth, realizing a sense of justice in the context of humanizing humans. Fifth, as an effort to equalize income. Keywords: Upah (Ujrah), Tafsir